Does corruption affect access to bank credit for micro and small businesses? Evidence from European MSMEs - Emma Galli; Danilo V. Mascia; Stefania P. S. Rossi (Asian Development Bank Institute (ADBI), 2017)
In this paper, we aim to assess how a specific socio-institutional environment, identified according to the level of corruption, may affect the access to credit for micro, small, and medium-sized enterprises (MSMEs). Using a sample of 68,115 observations - drawn from the ECB-SAFE survey - related to MSMEs chartered in 11 euro area countries during the period 2009-2014, we investigate whether the level of corruption affects their demand for bank loans. Overall, we find that the degree of corruption seems to play a role in the applications for bank loans when small firms are under investigation. Interestingly, results highlight that small businesses chartered in highly corrupt countries face a greater probability of self-restraint regarding their loan applications (about 7.4%) than small firms located in low-corruption economies (around 6%). The results are robust to various model specifications and econometric methodologies. Our findings suggest that anti-corruption policies and measures enhancing transparency in the economy may be crucial in reducing the negative spillovers generated by a low-quality institutional environment on the access to credit by small firms.
Keywords: G20; G21; G30; G32; D73; 330; credit access; bank loans; MSMEs; corruption